Multi-stakeholder perspectives of community pharmacies’ extended services in Al Baha province, Saudi Arabia: A qualitative study - Khalid S. Alghamdi; Mahdi H. Alsugoor; Max Petzold; Laith Hussain-Alkhateeb; Christina Ljungberg Persson (Global Public Health)
Community pharmacies have expanded to include new services such as health screenings and medication reviews. However, developing and implementing new applications tends to be challenging and entails comprehensive planning by multiple stakeholders. This qualitative study explores stakeholders’ perspectives of these new services and identifies perceived barriers or facilitators for implementing practice changes. The study held four focus group discussions with 27 stakeholders and was conducted in Al Baha province, Saudi Arabia. Participants described community pharmacy services as traditional and limited to dispensing prescriptions. Several barriers were identified, including a lack of public awareness, public privacy and confidentiality concerns, and inadequate communication and collaboration between community pharmacists and physicians. According to the participants, free training programmes and continuing education for community pharmacists (with a focus on independent and small-chain community pharmacies) and financial support from the government could facilitate extending the roles played by community pharmacists. Another suggestion was that implementing standards for accreditation could create a competitive environment for community pharmacies, granting them well-deserved privileges and enhancing public confidence in the quality and safety of pharmaceutical care. Developing interprofessional policy is also vital, as this would allow community pharmacies to integrate into the health system.